2007
DOI: 10.1016/j.ejso.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sentinel lymph node (SLN) status in primary breast cancer by prospective use of immunohistochemistry increases the rate of micrometastases and isolated tumour cells: Analysis of 174 patients after SLN biopsy

Abstract: Running title: Prospective use of immunohistochemistry ... Key words: primary breast cancer, sentinel lymph node biopsy, immunohistochemistry, isolated tumour cells and non-sentinel lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Thus, IHC resulted in change of lymph node status from negative to positive and ultimately changed the stage in 1 (2%) of 52 patients. Similar results have been described by other studies, although these studies were not exclusive to lobular carcinoma [4,26]. In the Cserni et al [6] study considering ITCs as negative nodes, the actual change in lymph node status by adding an additional step of IHC was in 15% cases, a much higher rate than 2% demonstrated in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, IHC resulted in change of lymph node status from negative to positive and ultimately changed the stage in 1 (2%) of 52 patients. Similar results have been described by other studies, although these studies were not exclusive to lobular carcinoma [4,26]. In the Cserni et al [6] study considering ITCs as negative nodes, the actual change in lymph node status by adding an additional step of IHC was in 15% cases, a much higher rate than 2% demonstrated in our study.…”
Section: Discussionsupporting
confidence: 91%
“…SLN can be assessed intraoperatively: imprint cytology, scrape preparations, and/ or cryosections have been described as equally helpful with an overall sensitivity of nearly 60% [2]. The sensitivity of intraoperative analysis is greatly dependent on the average size of metastatic deposits [3,4]. It has been demonstrated that SLN biopsy procedure is an accurate method for axillary staging in patients with invasive lobular carcinoma [5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with unifocal primary breast cancer (T < 3cm) and a clinical negative axilla were included prospectively from March 2001 to March 2003 at the department of Surgery in Helsingborg within the National Swedish Sentinel Node Study including a protocol for evaluation of prospective use of immunohistochemistry (IHC) for diagnosis of sentinel lymph node metastasis (29) . The present study included a protocol for consecutive immunohistochemical evaluation of all examined sentinel lymph nodes and was closed when the National Guidelines recommended IHC only in doubtful cases.…”
Section: Methodsmentioning
confidence: 99%
“…The present study included a protocol for consecutive immunohistochemical evaluation of all examined sentinel lymph nodes and was closed when the National Guidelines recommended IHC only in doubtful cases. The details of the protocol have been described elsewhere (29). The study was approved by the Ethics Committee at Lund University, Lund, Sweden and written informed consent was obtained from all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with either of these in one or more lymph node(s) had significantly reduced overall survival compared to patients who remained node negative after serial sections and immunohistochemistry. The importance of isolated tumor cells in lymph nodes has been reported not only in esophageal cancer [181,[184][185][186][187]189], but also in several studies of gastric cancer [196,197], melanoma [198], breast cancer [199][200][201][202], colorectal cancer [203][204][205], and non-small-cell lung cancer [206]. Lymph nodes containing isolated tumor cells should not be designated pN0(i+) as per the AJCC's breast cancer staging system.…”
Section: Lymphatic Spreadmentioning
confidence: 99%